2008
DOI: 10.1007/s10620-008-0572-8
|View full text |Cite
|
Sign up to set email alerts
|

Gastric Hyperplastic Polyps: A Review

Abstract: Hyperplastic polyps represent the commonest polyp encountered in the stomach. They occur in patients of either gender and are commoner in the seventh decade of life. They are usually asymptomatic, small (less than 1 cm in diameter), solitary lesions occurring in the antrum but can present with dyspepsia, heartburn, abdominal pain, or upper gastrointestinal (GI) bleeding leading to anemia. Hyperplastic polyps almost never occur in normal gastric mucosa and are most commonly associated with chronic gastritis (He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
90
0
6

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(101 citation statements)
references
References 37 publications
5
90
0
6
Order By: Relevance
“…In our study HPs were the most common type of polyps seen in the stomach; this finding is consistent with many previous reports (10,16,17,22,23). In the study of Carmack et al (3) HPs were seen in <15% of all polyps, they compared studies from different countries and stated that as HPs are associated with H. pylori infection, particularly atrophic gastritis the continuing decline of H. pylori infection and atrophic gastritis in the United States, as well as the simultaneous increase in FGPs, may have contributed to the low relative prevalence of HPs detected in their population.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In our study HPs were the most common type of polyps seen in the stomach; this finding is consistent with many previous reports (10,16,17,22,23). In the study of Carmack et al (3) HPs were seen in <15% of all polyps, they compared studies from different countries and stated that as HPs are associated with H. pylori infection, particularly atrophic gastritis the continuing decline of H. pylori infection and atrophic gastritis in the United States, as well as the simultaneous increase in FGPs, may have contributed to the low relative prevalence of HPs detected in their population.…”
Section: Discussionsupporting
confidence: 93%
“…Large HPs, up to 9 cm, have been reported (16). HPs are usually seen in older patients (seventh decade) with a slight female preponderance (17), which was also the case in our series. However HPs were also the commonest type of polyps seen in the study that included patients less than 21 years reported by Attard et al (18).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Hyperplastic polyps account for approximately 75% of all gastric polyps (8,15,16). Likewise, the majority of polyps in our study (83.9%) was hyperplastic.…”
Section: Discussionsupporting
confidence: 64%
“…Buyukasik et al reviewed a total of 66 upper gastrointestinal polyps from 59 patients and found esophageal polyps to be less common as compared to gastric and duodenal polyps [29 in the Hyperplastic polyps of the gastric corpus and antrum usually develop in association with chronic gastritis but the pathogenesis of esophageal hyperplastic polyps is still not fully understood [10,11]. However, there is evidence to suggest that the lesion develops as a result of mucosal regenerative response to surrounding mucosal injury [5,6,8].…”
Section: Discussionmentioning
confidence: 99%